2015
DOI: 10.2527/jas.2015-9022
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of γ-glutamyl transferase activity in cow milk throughout lactation and relationships with metabolic conditions and milk composition1

Abstract: The main objective of this experiment was to study the γ-glutamyl transferase (GGT) activity in milk during lactation and its relationship with metabolic status of dairy cows, milk yield, milk composition, and cheesemaking properties. The study was performed in a tied stall barn and involved 20 lactations from 12 healthy multiparous Italian Friesian dairy cows. During lactation starting at d 10, milk samples were collected weekly and analyzed for composition, somatic cells count, titratable acidity, and milk c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In mallards, egg laying activity significantly influences serum enzyme activity and GGT activity was reported to be elevated tenfold compared to other reproductive periods (Fairbrother et al, 1990). In cattle, GGT was identified as one of the enzymes found in milk and was found active during lactation but with no change in plasma GGT during this process (Calamari et al, 2015). Yet, the reason for GGT elevation in female green turtles before the nesting activity itself, is yet to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…In mallards, egg laying activity significantly influences serum enzyme activity and GGT activity was reported to be elevated tenfold compared to other reproductive periods (Fairbrother et al, 1990). In cattle, GGT was identified as one of the enzymes found in milk and was found active during lactation but with no change in plasma GGT during this process (Calamari et al, 2015). Yet, the reason for GGT elevation in female green turtles before the nesting activity itself, is yet to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a positive correlation of BHBA was observed with ALT, AST and LDH and negative correlations was observed between plasma BHBA and TC levels. Calamari et al (2015) studied the relationship of GGT activity in milk with EB and milk yield in healthy cows and found that GGT activity was in decreasing trend during early lactation period until second month. They found negative correlation between milk yield and BUN and positive correlation between glucose and GGT activity.…”
Section: Blood Biochemical Parameters In Relation To Energy Balance M...mentioning
confidence: 99%
“…Human milk exerts direct pharmacologic relaxation effects and provides better antioxidant protection compared with infant formulas because of the presence of specific enzymatic components, such as human SOD (Lugonja et al 2013). The previous study showed that an important effect of lactation stage on milk c-glutamyl transferase (GGT) activity, and a positive relationship between GGT activity and milk protein concentration was observed, which could influence protein synthesis, as well as protein composition, with possible implications for cheese-making properties related to the milk protein fractions (Calamari et al 2015). The time-dependent alterations of IgA, IgG, IgM, the C3, C4 protein and CuZn-SOD in human breast milk collected in the diurnal and nocturnal colostrum were observed by the studies of França and Nicomedes (2010).…”
Section: Changes Of Sod Activity In the Colostrum During Postpartum Lmentioning
confidence: 99%